Compensatory control and religious beliefs: a registered replication report across two countries. Issue 3 (2nd September 2018) - Hoogeveen, Suzanne; Wagenmakers, Eric-Jan; Kay, Aaron C.; Van Elk, Michiel
ABSTRACT: Compensatory Control Theory (CCT) suggests that religious belief systems provide an external source of control that can substitute a perceived lack of personal control. In a seminal paper, it was experimentally demonstrated that a threat to personal control increases endorsement of the existence of a controlling God. In the current registered report, we conducted a high-powered ( N = 829) direct replication of this effect, using samples from the Netherlands and the United States (US). Our results show moderate to strong evidence for the absence of an experimental effect across both countries: belief in a controlling God did not increase after a threat compared to an affirmation of personal control. In a complementary preregistered analysis, an inverse relation between general feelings of personal control and belief in a controlling God was found in the US, but not in the Netherlands. We discuss potential reasons for the replication failure of the experimental effect and cultural mechanisms explaining the cross-country difference in the correlational effect. Together, our findings suggest that experimental manipulations of control may be ineffective in shifting belief in God, but that individual differences in the experience of control may be related to religious beliefs in a way that is consistent with CCT.